Educational sociology and its impact on learners' behavior (Journal of the College of Basic Education, 2025)
As is known, sociology is concerned with the theoretical and applied study of social facts and phenomena within the framework of theoretical and methodological approaches intended to explain and subsequently understand them. It is a science that attempts to study society from all its aspects. Because society has evolved and its primary characteristic has become complexity, resulting in a multitude of societal topics and events and their diversity, and because the characteristic of the era is specialization, general sociology has been unable to grasp all of these topics. This has led to the emergence of new branches of this science, each of which attempts to study an aspect of these phenomena according to the scientific methodology, techniques, and research tools appropriate for each specialty or branch.